1995
DOI: 10.2105/ajph.85.11.1538
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for HIV-1 seroconversion among injection drug users: a case-control study.

Abstract: OBJECTIVES. A nested case-control study was conducted in Miami, Fla, to determine risk factors associated with human immunodeficiency virus type 1 (HIV-1) seroconversion among injection drug users. METHODS. The study identified 21 incident cases of HIV-1 infection and 76 unmatched controls from two longitudinal cohorts of injection drug users. One cohort consisted of individuals who originally had been recruited from treatment centers; a second cohort was recruited from the "street." Logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 33 publications
2
18
1
Order By: Relevance
“…Consistent with other studies (Chawarski, Mazlan, & Schottenfeld, 2006;Chitwood et al, 1995;Panda et al, 2005;Tuan et al, 2007), our findings confirm that unsafe injection behaviors, such as sharing needles or injection equipment, are the predominate modes of acquisition of HIV-1. Moreover, many studies in western countries indicated that unprotected sex with multiple partners and sex in exchange for drugs were common among IDUs (Chawarski et al, 2006;Chitwood et al, 1995;Shaboltas et al, 2006;Vassilev et al, 2006;Zhao et al, 2006). Such risk sexual behaviors were bridges for HIV transmission from IDUs to non-injecting sexual partners (Tuan et al, 2007).…”
Section: Severity Of Dependence and Risky Behaviors Associated With Hsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies (Chawarski, Mazlan, & Schottenfeld, 2006;Chitwood et al, 1995;Panda et al, 2005;Tuan et al, 2007), our findings confirm that unsafe injection behaviors, such as sharing needles or injection equipment, are the predominate modes of acquisition of HIV-1. Moreover, many studies in western countries indicated that unprotected sex with multiple partners and sex in exchange for drugs were common among IDUs (Chawarski et al, 2006;Chitwood et al, 1995;Shaboltas et al, 2006;Vassilev et al, 2006;Zhao et al, 2006). Such risk sexual behaviors were bridges for HIV transmission from IDUs to non-injecting sexual partners (Tuan et al, 2007).…”
Section: Severity Of Dependence and Risky Behaviors Associated With Hsupporting
confidence: 92%
“…Our findings indicated that perception of heroin-dependent syndromes increase the risk of conducting bloodborne virus transmitted behaviors among IDUs, might due to the craving for drugs at times when heroin-dependent injectors were in withdrawal (Gossop et al, 1993b). Consistent with other studies (Chawarski, Mazlan, & Schottenfeld, 2006;Chitwood et al, 1995;Panda et al, 2005;Tuan et al, 2007), our findings confirm that unsafe injection behaviors, such as sharing needles or injection equipment, are the predominate modes of acquisition of HIV-1. Moreover, many studies in western countries indicated that unprotected sex with multiple partners and sex in exchange for drugs were common among IDUs (Chawarski et al, 2006;Chitwood et al, 1995;Shaboltas et al, 2006;Vassilev et al, 2006;Zhao et al, 2006).…”
Section: Severity Of Dependence and Risky Behaviors Associated With Hsupporting
confidence: 90%
“…Of the more than 150,000 AIDS cases reported among women nationwide, through December 2002, injecting drug use accounted directly for 39% of cases (Centers for Disease Control and Prevention, 2003). Early research among predominantly male injection drug users (IDU) documented risk factors for HIV infection, including frequency of injection, number of injections shared or needle sharing, early age of initiation, cocaine injection, and shooting gallery attendance (Chaisson et al, 1989;Chitwood et al, 1995;Friedland et al, 1985;Moss et al, 1994;Schoenbaum et al, 1989;Vlahov et al, 1990). Later studies, however, suggested that female and male IDU engaged in injection risk behavior differently (Bennett et al, 2000;Dwyer et al, 1994;Gollub et al, 1998;Miller and Neaigus, 2001) and that risk factors for HIV infection among IDU differed between the sexes (Bruneau et al, 2001;Kral et al, 1997;Strathdee et al, 2001;van Ameijden et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Substance abuse can lead to high-risk sexual behaviors by affecting decision making, compromising judgment, decreasing the likelihood of condom use, and increasing the likelihood of sex-for-drug exchanges and injection drug use. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Yet, research on non-injection drug use and HIV/STIs has lagged considering its importance in the current HIV/STI epidemic.Taken together, these findings mirror changing patterns of transmission of HIV/STIs in the general population. In the early stages of the HIV/STI epidemic, the most common patterns of transmission were injection drug use (approximately one quarter of AIDS cases) and male-tomale sex (two thirds of AIDS cases).…”
mentioning
confidence: 99%